The Phytogeographic History of Common Walnut in China - Feng, Xiaojia; Zhou, Huijuan; Zulfiqar, Saman; Luo, Xiang; Hu, Yiheng; Feng, Li; Malvolti, Maria E.; Woeste, Keith; Zhao, Peng (Frontiers in Plant Science, 2018)
Common walnut (Juglans regia L.) is an economically important hardwood tree species cultivated worldwide for its high quality wood and edible nuts. It is generally accepted that after the last glaciation J. regia survived and grew in almost completely isolated stands in Asia, and that ancient humans dispersed walnuts across Asia and into new habitats via trade and cultural expansion. The history of common walnut in China is a matter of debate, however. We estimated the genetic diversity and spatial genetic structure of 31 walnut populations sampled across its Chinese range using 22 microsatellite markers (13neutral and 9 non-neutral). Using historical data and population genetic analysis, including approximate Bayesian analysis (ABC), we reconstructed the demographic history of J. regia in China. The genetic data indicated the likely presence of J. regia in glacial refugia in the Xinjiang province (northwest China), northeastern China (Beijing, Shandong, and Changbai Mountains), central China (Qinling and Baishan Mountains and Xi'an), and southwestern China (Tibet, Yunnan, Guizhou, and Sichuan provinces). Based on DIY-ABC analysis, we identified three ancient lineages of J. regia in China. Two lineages (subpopulation A and subpopulation B+C) diverged about 2.79 Mya, while southwestern China, and Qinling and Baishan Mountains lineages diverged during the Quaternary glaciations (about 1.13 Mya). Remnants of these once-distinct genetic clusters of J. regia may warrant ecological management if they are to be retained as in situ resources. A population size expansion in northeastern China was detected in the last five centuries. The present distribution of walnut in China resulted from the combined effects of expansion/contraction from multiple refugia after the Last Glacial Maximum and later human exploitation.